Canadian Public Health Laboratory Network laboratory Guidelines for the Use of Serological Tests (excluding point-of-care tests) for the Diagnosis of Syphilis in Canada. (2015) - Levett, Paul N; Fonseca, Kevin; Tsang, Raymond SW; Kadkhoda, Kamran; Serhir, Bouchra; Radons, Sandra M; Morshed, Muhammad
Abstract : Syphilis, caused by the bacterium Treponema pallidum subsp. pallidum, is an infection recognized since antiquity. It was first reported at the end of the 15th century in Europe. Infections may be sexually transmitted as well as spread from an infected mother to her fetus or through blood transfusions. The laboratory diagnosis of syphilis infection is complex. Because this organism cannot be cultured, serology is used as the principal diagnostic method. Some of the issues related to serological diagnoses are that antibodies take time to appear after infection, and serology screening tests require several secondary confirmatory tests that can produce complex results needing interpretation by experts in the field. Traditionally, syphilis screening was performed using either rapid plasma reagin or Venereal Disease Research Laboratory tests, and confirmed by treponemal tests such as MHA-TP, TPPA or FTA-Abs. Currently, that trend is reversed, ie, most of the laboratories in Canada now screen for syphilis using treponemal enzyme immunoassays and confirm the status of infection using rapid plasma reagin or Venereal Disease Research Laboratory tests; this approach is often referred to as the reverse algorithm. This chapter reviews guidelines for specimen types and sample collection, treponemal and non-treponemal tests utilized in Canada, the current status of serological tests for syphilis in Canada, the complexity of serological diagnosis of syphilis infection and serological testing algorithms. Both traditional and reverse sequence algorithms are recommended and the algorithm used should be based on a combination of local disease epidemiology, test volumes, performance of the proposed assays and available resources.